The impact of COVID-19 on financing decisions of SMEs in Vietnam - An H.K. Vo,; Trang T.T. Truong,; Khoa D. Huynh, (Asian Academy of Management Journal, 2022)
The coronavirus disease (COVID-19) pandemic has had a massive impact on the economy around the world. To shed light on how COVID-19 is affecting the bank loan financing decisions of small and medium-sized enterprises (SMEs) in Vietnam, we conducted a survey with the participation of representatives come from 92 SMEs in Ho Chi Minh City, Vietnam in the period from March to April 2020. Employing logistic regression, we find that the risk perception of COVID-19 is a significant factor that helps predict SMEs’ bank loan financing decisions. This study not only contributes to management literature regarding firm’s financing decisions but also assists policymakers in introducing policies related to SMEs.